Carbon-coal composite functional material as well as preparation method and application thereof
By mixing agricultural and forestry biomass waste and lignite in an appropriate proportion and pyrolyzed under low-temperature aerobic conditions, a carbon-coal composite functional material with large specific surface area, dense pores, high humic acid content and rich oxygen-containing functional groups was prepared, which solved the problem of insufficient adsorption stability of biochar when adsorbing ammonia and hydrogen sulfide, and achieved efficient adsorption and stable fixation of NH3/NH4+.
Patent Information
- Application Number
- CN202411932293.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-26
- Publication Date
- 2025-03-14
- Estimated Expiration
- 2044-12-26
AI Technical Summary
When biochar adsorbs odorous gases such as ammonia and hydrogen sulfide, its pore structure becomes rich as the pyrolysis temperature increases, but the number of oxygen-containing functional groups on the surface decreases, resulting in insufficient adsorption stability.
By mixing agricultural and forestry biomass waste and lignite in an appropriate proportion and pyrolyzed under low-temperature aerobic conditions, a carbon-coal composite functional material with large specific surface area, dense pores, high humic acid content and rich oxygen-containing functional groups was prepared.
This method not only improves the utilization value of biochar and lignite, but also achieves firm fixation of nitrogen through the chemical reaction of functional groups, significantly improving the adsorption stability and efficiency of NH3/NH4+.
Smart Images

Figure BDA0005210645210000051 
Figure BDA0005210645210000071 
Figure HDA0005210645220000011
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of solid waste resource utilization and relates to a carbon-coal composite functional material and a preparation method and application thereof. Background Art
[0002] Biochar is a carbon-rich material with complex microstructure, special physical and chemical properties, and high aromatization, which is obtained by thermochemical conversion of various organic waste materials under anaerobic or anoxic conditions. Biochar prepared from agricultural and forestry biomass wastes such as straw and wood chips has become an ideal new type of high-efficiency adsorbent due to its large specific surface area, developed micropores, and high surface charge density. It is widely used in wastewater treatment, ecological restoration, and environmental protection, and has good application prospects in soil improvement, carbon fixation, and pollutant adsorption and degradation. A large amount of ammonia is emitted during the combustion of biomass, fossil fuels, drug production, and livestock and poultry manure treatment. Excessive emission of ammonia will cause great harm to humans, animals, and the ecological environment. Studies have shown that biochar has a good adsorption effect on odorous gases such as ammonia, hydrogen sulfide, and volatile organic compounds. Its mechanism of action is closely related to the specific surface area, microporous structure, and functional group content of biochar. In the process of preparing biochar, as the pyrolysis temperature increases, the pore structure of biochar becomes richer and the specific surface area becomes larger, but the number of surface oxygen-containing functional groups, especially acidic functional groups, decreases, resulting in its NH3 / NH4 + In actual application, the adsorption of NH3 / NH4 is weakened only by the physical structure characteristics of biochar. + It is not stable and firm enough, so it is necessary to study the combination of biochar and suitable functional materials to improve the adsorption stability. Lignite is a weakly acidic carbon-containing material with less pore structure and small specific surface area. It has weak physical adsorption capacity for pollutants, but its surface contains abundant active groups such as carboxyl, quinone, carbonyl, methoxyl and humic acid macromolecules. The functional groups carried on the surface of lignite can react with NH3 / NH4 + A chemical reaction occurs to firmly fix nitrogen. Therefore, it is of great significance to explore a composite functional material with complementary performance advantages of biochar and lignite and to build an efficient functional system to solve the above problems. Summary of the invention
[0003] The purpose of the present invention is to provide a carbon-coal composite functional material and its preparation method and application. The present invention uses lignite and biochar to mix to prepare the composite functional material, which can complement the performance advantages of biochar and lignite and improve the utilization value of the two materials.
[0004] The present invention provides a method for preparing a biochar and lignite modified carbon-coal composite functional material. Agricultural and forestry biomass waste and lignite are used as raw materials. Biochar prepared from agricultural and forestry biomass waste and lignite are mixed and modified by low-temperature aerobic pyrolysis to obtain a carbon-coal composite functional material. The composite material has good biocompatibility and complementary performance advantages, which can make up for the limitations of a single material, provide a theoretical basis for the creation of biochar and lignite composite functional materials, and achieve efficient utilization of biochar and lignite and pollutant reduction and control.
[0005] In order to achieve the above object, the present invention provides a method for preparing a carbon-coal composite functional material, comprising the following steps: 1) crushing and sieving lignite and agricultural and forestry biomass waste respectively;
[0006] 2) pyrolyzing the agricultural and forestry biomass waste obtained in step 1) under inert atmosphere conditions to obtain biochar material;
[0007] 3) washing the biochar material with deionized water until neutral, then air-drying and crushing;
[0008] 4) The biochar material treated in step 3) is mixed with the lignite treated in step 1), and subjected to low-temperature aerobic pyrolysis to obtain a carbon-coal composite functional material.
[0009] In the present invention, in step 1), the agricultural and forestry biomass waste needs to be air-dried and air-dried in advance, and the pH, sulfur content, and humic acid content of the lignite need to be measured to ensure that the quality of the above raw materials is qualified.
[0010] In the above-mentioned preparation method, the agricultural and forestry biomass waste is at least one of rice straw, corn straw, wheat straw, soybean straw, rice straw and tree branch sawdust;
[0011] The particle size of the lignite screened may be 0.2 to 0.5 mm;
[0012] The particle size of the sieved agricultural and forestry biomass waste can be 1 to 2 mm;
[0013] The biochar material may have a sieved particle size of 0.2 to 0.5 mm, and the biochar material is sieved so as to be uniformly mixed with the lignite.
[0014] In the above preparation method, the pyrolysis treatment is as follows: the agricultural and forestry biomass waste obtained by the treatment in step 1) is placed in a tubular furnace through which the inert gas is passed, and the temperature is increased to 550-650°C at a rate of 5-10°C / min, and pyrolyzed for 1-2h to obtain the biochar material; specifically, the heating rate can be 10°C / min, the pyrolysis temperature can be 600°C, and the pyrolysis time can be 2h;
[0015] The inert gas includes nitrogen.
[0016] In the present invention, the biochar material prepared by pyrolysis in step 2) is alkaline, and the subsequent direct blending and compounding with the lignite will affect the acidic functional group content of the lignite, so the biochar material needs to be cleaned in step 3).
[0017] In the above preparation method, in step 4), the mass ratio of the biochar material to the lignite can be 1:0.5-2, specifically 1:1, 1:0.5-1 or 1:1-2.
[0018] In the above preparation method, in step 4), the low-temperature pyrolysis is performed after the temperature is raised to 175-250°C at a heating rate of 5-10°C / min; specifically, the heating rate may be 10°C / min;
[0019] The conditions of the low-temperature pyrolysis are as follows: pyrolysis under aerobic conditions, the temperature can be 175-250°C (specifically 225°C, 175-225°C, 225-250°C), and the time can be 0.5-2h (specifically 2h or 1-2h).
[0020] In the above-mentioned preparation method, the step 4) further comprises the steps of crushing and sieving after the low-temperature pyrolysis; wherein the sieving particle size can be 0.2 to 0.5 mm, so as to be compatible with NH4 + Full contact for adsorption reaction.
[0021] The present invention also provides a carbon-coal composite functional material prepared by the above preparation method.
[0022] The carbon-coal composite functional material of the present invention is used for adsorbing NH3 / NH4 + of substances.
[0023] In the present invention, the carbon-coal composite functional material can be applied to wastewater treatment, ecological restoration, environmental protection, biomass combustion, fossil fuel combustion, drug production and livestock and poultry manure treatment, etc. + Contaminant materials.
[0024] The present invention further provides a method for removing NH4 in a solution by using the above-mentioned carbon-coal composite functional material. + The method comprises the following steps:
[0025] The carbon-coal composite functional material is added to a NH4 + The solution was filtered after the reaction to remove NH4 + .
[0026] In the above method, the NH4 + NH4 in solution + The concentration can be 0.001~0.02mol / L;
[0027] The reaction temperature is room temperature, and the reaction time can be 20 to 24 hours, specifically 24 hours;
[0028] The filtration uses a nylon filter, and the pore size of the filter membrane can be 0.4-0.5 μm, specifically 0.45 μm.
[0029] The present invention has the following beneficial effects:
[0030] 1. The present invention uses agricultural and forestry biomass waste (such as rice straw) and lignite as raw materials, mixes them evenly in an appropriate proportion, and pyrolyzes them at low temperature under aerobic conditions to prepare a modified carbon-coal composite material with a large specific surface area, dense pores, high humic acid content, and rich oxygen-containing functional groups.
[0031] 2. The biochar and lignite modified carbon-coal composite functional materials prepared by this method are micron-sized. For example, the modified carbon-coal composite functional materials prepared by rice straw and lignite at 1:1, 225℃, and 2h have a pore size of about 0.6-1.8μm and a micropore area of about 0.3-1.7μm. 2 , rich pores, relatively uniform distribution, with strong adsorption capacity, for NH4 + It has a synergistic reduction effect, achieving the synergistic efficiency, harmless treatment and resource utilization of straw and lignite.
[0032] 3. The biochar and lignite modified carbon-coal composite functional material of the present invention has no negative impact on the adsorption performance of the biochar. In a specific example, the biochar material and lignite are compounded in a ratio of 1:1 for absorbing NH4 + The effects are remarkable, and the + The adsorption rate reached 20.81%. BRIEF DESCRIPTION OF THE DRAWINGS
[0033] Figure 1 This is a scanning electron microscope image of the biochar material prepared in Example 1 of the present invention, wherein Figure 1 (a)-(c) are scanning images under an electron microscope at ×10μm, ×1μm, and ×500nm magnifications, respectively.
[0034] Figure 2 This is a scanning electron microscope image of the lignite material prepared in Example 1 of the present invention, wherein Figure 2 (a)-(c) are scanning images under an electron microscope at ×10μm, ×1μm, and ×500nm magnifications, respectively.
[0035] Figure 3 This is a scanning electron microscope image of the modified carbon-coal composite functional material prepared in Example 1 of the present invention, wherein Figure 3(a)-(c) are scanning images under an electron microscope at ×10μm, ×1μm, and ×500nm magnifications, respectively.
[0036] Figure 4 The modified carbon-coal composite functional material prepared in Example 1 of the present invention adsorbs NH4 + SEM images of Figure 4 (a)-(c) are scanning images under an electron microscope at ×10μm, ×1μm, and ×500nm magnifications, respectively. DETAILED DESCRIPTION
[0037] Unless otherwise specified, the experimental methods used in the following examples are conventional methods.
[0038] Unless otherwise specified, the materials and reagents used in the following examples can be obtained from commercial sources.
[0039] In order to better explain the present invention and facilitate understanding, the present invention is described in detail below through specific implementation methods in conjunction with the accompanying drawings and appendixes.
[0040] Example 1
[0041] The method for preparing the carbon-coal composite functional material provided in this embodiment comprises the following steps:
[0042] (1) A certain amount of rice straw that has been dried, shredded, and sieved to 1.0-2.0 mm is placed in a tubular furnace, heated to 600 °C at a rate of 10 °C / min under nitrogen protection, and pyrolyzed for 2 h. The product is then washed with deionized water and dried in an oven to obtain rice straw biochar, such as Figure 1 The figure shows the scanning electron microscope image of the prepared rice straw biochar. The surface of the prepared biochar has a large number of pores and rich microporous structures. The pore size of the prepared biochar material is 1.0-3.0 μm, and the micropore area is 0.7-2.5 μm. 2 .like Figure 2 The scanning electron microscope image of lignite is shown. The surface pores of lignite material are far less than those of straw biochar and the pore structure is poor. The pore size is 0.5-1.5 μm, and the micropore area is 0. 2 .
[0043] (2) The biochar material and lignite were composite modified at a composite ratio of 1:1. 40 g of rice straw biochar and 40 g of lignite were weighed and mixed evenly and transferred to a forced air drying oven for low-temperature pyrolysis at 225 °C for 2 h under aerobic conditions. After the reaction was completed, the material was cooled to room temperature (25 °C) to obtain a dry lump of carbon-coal composite functional material, which was placed in a sealed bag to remove air and crushed. The powdered biochar and lignite-modified carbon-coal composite functional material was sieved through a 60-mesh sieve, such as Figure 3This is a scanning electron microscope image of a carbon-coal composite functional material modified from biochar and lignite. It can be seen from the figure that the prepared carbon-coal composite material has a rough surface, abundant binding sites, and is easy to adsorb and attach. It has a large number of irregularly shaped tiny pore structures. Compared with biochar materials, the pores are denser, and it can be seen that the microporous surface structure is complex, which may be a large number of functional group binding sites generated during low-temperature aerobic pyrolysis. The pore size of the prepared material is 0.6-1.8μm, and the micropore area is about 0.3-1.7μm 2 .
[0044] (3) Using biochar and lignite-modified carbon-coal composite functional materials to adsorb NH4 + ,like Figure 4 Modified carbon-coal composite functional materials for adsorption of NH4 + The scanning electron microscope image after the adsorption of NH4 + The surface pores of the composite material after adsorption have changed significantly, from the original irregular shape to a regular ellipse, which can absorb NH4 + The pore size of the final material is 0.3-1.0 μm, and the micropore area is about 0.2-0.9 μm. 2 Compared with before adsorption, the pore size and micropore area of the material are reduced, the roughness of the material structure is reduced, and particulate matter is attached to the surface, which proves that NH4 + Adsorption reaction occurs with modified carbon-coal composite functional materials.
[0045] (4) The adsorption of NH4 by biochar, lignite, carbon-coal composite functional materials, and carbon-coal composite functional materials can be compared in Table 1. + After the element changes of each material, the carbon-coal composite functional material and the adsorption of NH4 + After the reaction, the S content gradually decreased, proving that low-temperature pyrolysis and adsorption reactions are helpful for the removal of S. The contents of N, C, H, and O in the carbon-coal composite functional material after composite modification are basically the median of the contents of N, C, H, and O in the biochar material and the lignite material, proving that the two materials have good compatibility during the low-temperature aerobic pyrolysis modification of biochar and lignite. The biochar and lignite modified carbon-coal composite functional material has good compatibility in the adsorption of NH4 + After that, the N and H contents increased significantly, proving that NH4 + It was successfully attached to the carbon-coal composite functional material modified from biochar and lignite.
[0046] Table 1 Adsorption of NH by biochar, lignite, carbon-coal composite functional materials, and carbon-coal composite functional materials 4+ Elemental analysis
[0047]
[0048] Example 2
[0049] This embodiment is based on the embodiment 1, and the biochar and lignite in step (2) are adjusted to a single biochar.
[0050] Example 3 This example is based on Example 1, except that the biochar and lignite in step (2) are adjusted to single lignite.
[0051] Example 4
[0052] This example is based on Example 1, except that the rice straw biochar in step (1) is replaced with corn straw biochar.
[0053] Example 5
[0054] This embodiment is based on the embodiment 1, and the low-temperature decomposition temperature in step (3) is adjusted to 175°C.
[0055] Example 6
[0056] This embodiment is based on the embodiment 1, except that the low temperature decomposition temperature in step (3) is adjusted to 200°C.
[0057] Example 7
[0058] This embodiment is based on the embodiment 1, except that the low temperature decomposition temperature in step (3) is adjusted to 250°C.
[0059] Example 8
[0060] This embodiment is based on the embodiment 1, and the compounding ratio of straw biochar to lignite in step (3) is changed from 1:1 to 1:2.
[0061] Example 9
[0062] This embodiment is based on the embodiment 1, and the compounding ratio of straw biochar to lignite in step (3) is changed from 1:1 to 2:1.
[0063] Example 10
[0064] This example is based on Example 1, except that the low-temperature pyrolysis time in step (3) is adjusted from 2 h to 0.5 h.
[0065] Embodiment 11
[0066] This example is based on Example 1, except that the low-temperature pyrolysis time in step (3) is adjusted from 2 h to 1 h.
[0067] Example 12
[0068] This example is based on Example 1, except that the low-temperature pyrolysis time in step (3) is adjusted from 2 h to 1.5 h.
[0069] Embodiment 13
[0070] The materials prepared by the above-mentioned examples 1-12 are used to remove NH3 / NH4 + The solution is as follows:
[0071] Adsorption of NH4 + Experiment: The functional materials prepared in Examples 1-12 were added into conical flasks containing NH4Cl solutions of the same concentration, and the modified carbon-coal composite functional materials were tested for NH4 + Adsorption capacity. Place in a constant temperature shaker set at a certain temperature and shake at 100 rpm for 24 hours. Filter through a 0.45 μm nylon filter to determine the remaining NH4 + The materials prepared in Examples 1-12 have a high concentration of NH4 + The adsorption effects are shown in Table 2.
[0072] Table 2 The effects of various materials on NH4 under different conditions + Adsorption results
[0073]
[0074] The above analysis of the adsorption effect fully demonstrates that the carbon-coal composite functional material modified by biochar and lignite improves the absorption of NH4 + When other conditions are the same and only the effect of pyrolysis time on the adsorption effect is considered, the difference in adsorption effect between pyrolysis time of 1h, 1.5h and 2h is small. Considering the time cost, no longer research is conducted. The optimal preparation process conditions obtained by the present invention are that the composite ratio of biochar to lignite is 1:1, the low-temperature pyrolysis temperature is 225℃, and the reaction time is 2h.
[0075] The biochar and lignite modified carbon-coal composite functional material prepared by the present invention has the characteristics of rich pores, complex micropore structure, rough surface, and easy contact and adsorption, which makes up for the shortcomings of biochar with few oxygen functional groups and lignite with few pores and smooth surface. The biochar and lignite modified carbon-coal composite functional material uses biochar and lignite as raw materials, which are sufficient and easy to obtain, and promotes the resource utilization of agricultural and forestry biomass waste and lignite.
[0076] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein with equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present invention.
Claims
1. A method for preparing a carbon-coal composite functional material, comprising the following steps: 1) crushing and sieving lignite and agricultural and forestry biomass waste respectively; 2) pyrolyzing the agricultural and forestry biomass waste obtained in step 1) under inert atmosphere conditions to obtain biochar material; 3) washing the biochar material with deionized water until it is neutral, then air-drying and crushing; 4) The biochar material treated in step 3) is mixed with the lignite treated in step 1), and subjected to low-temperature aerobic pyrolysis to obtain a carbon-coal composite functional material.
2. The preparation method according to claim 1, characterized in that: The agricultural and forestry biomass waste is at least one of rice straw, corn straw, wheat straw, soybean straw, tree branches and wood chips; The particle size of the sieved lignite is 0.2 to 0.5 mm; The particle size of the sieved agricultural and forestry biomass waste is 1.0 to 2.0 mm; The particle size of the biochar material after screening is 0.2-0.5 mm.
3. The preparation method according to claim 1 or 2, characterized in that: The pyrolysis treatment is as follows: the agricultural and forestry biomass waste obtained by the treatment in step 1) is placed in a tubular furnace through which the inert gas is passed, the temperature is raised to 550-650° C. at a rate of 5-10° C. / min, and pyrolyzed for 1-2 hours to obtain the biochar material; The inert gas includes nitrogen.
4. The preparation method according to any one of claims 1 to 3, characterized in that In step 4), the mass ratio of the biochar material to the lignite is 1:0.5-2.
5. The preparation method according to any one of claims 1 to 4, characterized in that: In step 4), the temperature is raised to 175-250° C. at a heating rate of 5-10° C. / min and then the low-temperature pyrolysis is performed; The conditions of the low-temperature pyrolysis are as follows: pyrolysis under aerobic conditions, the temperature is 175-250° C., and the time is 0.5-2 h.
6. The preparation method according to any one of claims 1 to 5, characterized in that: The step 4) further comprises the steps of crushing and sieving after the low-temperature pyrolysis; wherein the sieving particle size is 0.2 to 0.5 mm.
7. The carbon-coal composite functional material prepared by the preparation method according to any one of claims 1 to 6.
8. The carbon-coal composite functional material according to claim 7 absorbs NH3 / NH4 + application of substances.
9. A method for removing NH4 in a solution by using the carbon-coal composite functional material according to claim 7 + The method comprises the following steps: The carbon-coal composite functional material is added to a NH4 + The solution was filtered after the reaction to remove NH4 + .
10. The method according to claim 9, characterized in that The NH4 + NH4 in solution + The concentration is 0.001mol / L~0.02mol / L; The reaction temperature is room temperature and the reaction time is 20 to 24 hours; The filtration adopts a nylon filter, and the pore size of the filter membrane is 0.4-0.5 μm.
Citation Information
Patent Citations
Biochar modification method for improving ammonium nitrogen adsorption capability in soil / water
CN104689788A
Preparation method and application of alkali-soluble fly ash modified straw stalk biochar
CN114425303A
Preparation method and application of aquatic plant-based magnesium modified carbon material
CN115041136A
Oxidation-modified activated carbon fiber felt adsorbent, preparation method thereof and application of adsorbent to adsorption of low-concentration ammonia gas
CN118236974A
Surface modified coal compositions
WO2021119762A1